Pancreatic Mass Due to Fungal Infection Without Any Documented Pancreatitis – A Case Report - Das, Abhishek; Misra, Debashis; Ghosh, Ranajoy; Halder, Aniket (Archives of Clinical and Medical Case Reports, 2020)
45 year old male with history of regular alcohol use, but without any documented evidence of pancreatitis presented with features of biliary obstruction which an evaluation came out to be related to pancreatic head mass. Subsequent evaluation revealed candida infection of pancreas to be the reason for mass formation and biliary obstruction.